2019
DOI: 10.1158/1541-7786.mcr-18-0666
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor–Independent 1 Is a Tumor Suppressor Gene in Colorectal Cancer

Abstract: Colorectal cancer is the third most common cancer and the third leading cause of cancer death in the United States. Growth factor-independent 1 (GFI1) is a zinc finger transcriptional repressor responsible for controlling secretory cell differentiation in the small intestine and colon. GFI1 plays a significant role in the development of human malignancies, including leukemia, lung cancer, and prostate cancer. However, the role of GFI1 in colorectal cancer progression is largely unknown. Our results demonstrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…A similar scenario is found in solid tissues such as lung, inner ear hair epithelium, nervous system, and intestinal epithelium, in which Gfi1 function depends on the tissue, again suggesting a dual role for this transcription factor [16]. Two recent studies reported Gfi1 downregulation in colorectal cancer suggesting a tumor suppressor role in this tissue [17,20]. Our data can be explained by proposing a similar role for Gfi1 in prostate and breast cancer.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar scenario is found in solid tissues such as lung, inner ear hair epithelium, nervous system, and intestinal epithelium, in which Gfi1 function depends on the tissue, again suggesting a dual role for this transcription factor [16]. Two recent studies reported Gfi1 downregulation in colorectal cancer suggesting a tumor suppressor role in this tissue [17,20]. Our data can be explained by proposing a similar role for Gfi1 in prostate and breast cancer.…”
Section: Discussionsupporting
confidence: 85%
“…Tumor suppressor properties have been proposed for Gfi1 since its re-expression in cancer cell lines lacking Gfi1 function decreases cell proliferation [16,20]. We assessed the ability of Gfi1 to function as tumor suppressor gene in prostate and breast cancer cell lines.…”
Section: Gfi1 Re-expression Genes Decreases Cell and Tumor Growth Andmentioning
confidence: 99%
“…To investigate the underlying mechanism of SLC2A3 expression, we divided them into low-SLC2A3 expression group and high-SLC2A3 expression group based on SLC2A3 median expression level. Moreover, GSE17536(N = 177) and GSE17537 (N = 55) data (11)(12)(13)(14) were applied for further prognosis validation, which were from Gene Expression Omnibus (GEO) data (https://www.ncbi.nlm.nih.gov/geo/ query/acc.cgi?acc=GSE17536 and https://www.ncbi.nlm.nih. gov/geo/query/acc.cgi?acc=GSE17537).…”
Section: Data Miningmentioning
confidence: 99%
“…GFI1 is a kind of DNA binding zinc finger protein and it can mediate transcriptional repression through recruiting histone-modifying enzymes to its targets (31). Downregulation of GFI1 can promote inflammation-linked metastasis of colorectal cancer, and it is a tumor suppressor gene (32,33).Currently, we proved that GFI1 was down-regulated in HCC tissues and cells. Meanwhile, GFI1 interacted with the LINC00675 promoter via the three binding sites.…”
Section: Discussionmentioning
confidence: 88%